2014
DOI: 10.1093/infdis/jiu409
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota, Microbial Translocation, and Systemic Inflammation in Chronic HIV Infection

Abstract: Patients who have chronic HIV infection and are receiving suppressive ART display intestinal dysbiosis associated with increased microbial translocation and significant associations between specific taxa and markers of microbial translocation and systemic inflammation. This was an exploratory study, the findings of which need to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
389
6
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(427 citation statements)
references
References 49 publications
28
389
6
4
Order By: Relevance
“…Specifically, Rikenellaceae family members were depleted in patients who had chronic HIV infection relative to HIV-uninfected controls (46) and suppressed in IBD patients relative to healthy controls (45,47). Conversely, one study reported a higher abundance of Ruminococcaceae and Rikenellaceae and a decrease in the abundance of Prevotellaceae in the terminal ileum microbiota of subjects with ankylosing spondylitis (AS) compared with healthy controls (48).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Rikenellaceae family members were depleted in patients who had chronic HIV infection relative to HIV-uninfected controls (46) and suppressed in IBD patients relative to healthy controls (45,47). Conversely, one study reported a higher abundance of Ruminococcaceae and Rikenellaceae and a decrease in the abundance of Prevotellaceae in the terminal ileum microbiota of subjects with ankylosing spondylitis (AS) compared with healthy controls (48).…”
Section: Discussionmentioning
confidence: 99%
“…Faecalibacterium prausnitzii is of interest as it possesses antiinflammatory properties and is reduced in CD patients (30), in particular in those with ileal involvement (15). In addition, Corynebacterium and Erysipelotrichaceae are considered to be proinflammatory (31,32), and the Unweighted (C) (Kruskal-Wallis test P < 0.0001, Dunn's multiple comparisons test P < 0.0001) and weighted (D) (Kruskal-Wallis test P = 0.0011, Dunn's multiple comparisons test P < 0.01) beta diversity comparison within and between each group (Milwaukee cohort). *P < 0.05; ****P < 0.0001.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Ineffective glucose uptake mediated by the HIV-1 protein Tat (8) and microtubule disruption induced by the viral protein gp120 (7) are also thought to play a dominant role in the high level of enterocyte apoptosis observed in HIV-1-infected individuals (5,9). When associated with villous atrophy (10), this intestinal barrier disorganization causes disruption of epithelial tight junctions, resulting in the entry of microbial products into the bloodstream (a phenomenon also known as microbial translocation) (5,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Large quantities of microorganisms may thus survive at extraintestinal sites where microbial components such as peptidoglycan, lipoteichoic acid, lipopolysaccharide, flagellin, ribosomal RNA, and unmethylated CpG-containing DNA are usually absent (37). Ligation of nucleotide-binding oligomerization domains 1 and 2 (NOD1 and NOD2) (38,39) as well as TLR2, TLR4, TLR5, TLR6, and TLR9 (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) by these microbial products induces potent proinflammatory responses that have been proposed to mediate chronic immune activation and disease progression in the context of HIV-1 infection (11)(12)(13)(51)(52)(53).…”
mentioning
confidence: 99%